PENGARUH PENDAPATAN ORANG TUA TERHADAP TINGKAT PENDIDIKAN ANAK NELAYAN DI DESA KUALA KECAMATAN SELAKAU KABUPATEN SAMBAS - Dewi, Atikha Nur Setia; Aminuyati, Aminuyati; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
The objective of this study is to ascertain the correlation between parental income and the educational attainment of the offspring of fishermen. Descriptive research methodology in the form of relationship study research was employed. With a substantial sample size of 42, the population of this study consists of fishing families with school-aged children residing in Kuala Village, Selakau District, Sambas Regency. The method of data collection employs both documentary and indirect communication strategies. The data collection instruments utilized were questionnaires and documentation. The data processing method employs the Chi Squared value (X ²). The research results show that there is an influence of parents' income on children's education level. Based on calculations using the chi square formula, the calculated Chi square Chi Square table is (11.296 9.488). As a result, the null hypothesis (Ho) is denied in favor of the alternative hypothesis (Ha), which states that there is a correlation between the income of parents and the educational attainment of children of fishermen residing in Kuala Village, Selakau District, Sambas Regency